The Hubungan Paritas dan Preeklamsi dengan Kejadian BBLR di RSUD dr. M. Yunus Bengkulu Tahun 2017 - Nurul Khairani; Sanisahhuri Sanisahhuri; Suryani Suryani; Clara Putri Kendari (STIKes CHMK, 2020)
Short term impacts of Low Birth Weight (LBW) are metabolic disorders, immune disorders, circulatory system disorders, fluid and electrolyte disorders, and long term impacts are developmental disorders, growth disorders, speech disorders, communication disorders, communication disorders, neurological disorders, and cognition. This study aimed to determine the relationship between parity and preeclampsia with LBW incidence at dr. M. Yunus Hospital Bengkulu. This research used Analytical Survey with Cross Sectional design. The population in this study were mothers giving birth at dr. M. Yunus Hospital Bengkulu in 2017 there were 654 mothers. The sampling technique in this study used Simple Random Sampling with 87 mothers giving birth. In this study using secondary data that was data recorded in the register at dr. M. Yunus Hospital Bengkulu from January to December 2017. Data analysed by univariate and bivariate methods with Chi-Square (c2) statistical test. To determine the closeness of the relationship by using the Contingency Cofficient (C) statistical test. The results obtained from 87 mothers who gave birth, there were 58 mothers (66.7%) who did not have babies with LBW, 47 mothers (54%) with multiparous parity, and 72 mothers (82.8%) without preeclampsia. There was a significant relationship between parity with LBW incidence and there was a significant relationship between preeclampsia and LBW incidence at dr. M. Yunus Hospital Bengkulu. It is expected that dr. M. Yunus Hospital Bengkulu to be able to do health promotion to pregnant women about preventing LBW so that their knowledge increases and LBW incidence can be prevented. Keywords: LBW incidence, parity, preeclampsia